2022
DOI: 10.1108/jfra-07-2021-0205
|View full text |Cite
|
Sign up to set email alerts
|

R&D expenditure and managerial ownership: evidence from firms of high-vs-low R&D intensity

Abstract: Purpose Corporate managers spend on research and development (R&D) for reasons of growth and survival. However, they may be less willing to invest in R&D because of its long-term horizon, high failure rate and uncertain outcomes. This study aims to explore the extent to which managerial ownership influences R&D expenditure decisions. Design/methodology/approach Apart from the linear regression models, this study uses a semi-parametric quantile regression analysis for a sample of German non-financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The results of this study support research (Al-Ahdal et al, 2023a), it was found that managerial ownership has a positive influence on firm performance, because company managers have an important role in the company's progress. This is supported by research (Salema, 2023) which explains that the greater share ownership by directors and commissioners will increase firm performance, so this has a positive effect, while research conducted by (Hassanein et al, 2023) shows that managerial ownership has an effect negative impact on firm performance because there are two roles played by managers so that decisions taken will focus on personal interests rather than company goals. Management that has a dual role, namely as owner and manager, tends to be more careful in making decisions.…”
Section: Discussionmentioning
confidence: 86%
“…The results of this study support research (Al-Ahdal et al, 2023a), it was found that managerial ownership has a positive influence on firm performance, because company managers have an important role in the company's progress. This is supported by research (Salema, 2023) which explains that the greater share ownership by directors and commissioners will increase firm performance, so this has a positive effect, while research conducted by (Hassanein et al, 2023) shows that managerial ownership has an effect negative impact on firm performance because there are two roles played by managers so that decisions taken will focus on personal interests rather than company goals. Management that has a dual role, namely as owner and manager, tends to be more careful in making decisions.…”
Section: Discussionmentioning
confidence: 86%
“…Manso (2011) argues that managerial ownership provides managers greater job security and motivates them with higher tolerance for early failure of R&D activities. Hassanein et al. (2022) find that higher managerial ownership could increase firm R&D investment in firms with low R&D intensity.…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 86%
“…Manso (2011) argues that managerial ownership provides managers greater job security and motivates them with higher tolerance for early failure of R&D activities. Hassanein et al (2022) find that higher managerial ownership could increase firm R&D investment in firms with low R&D intensity. Thus, entrenched managers are more likely to apply more R&D investment to alleviate adverse financial status issues caused by high agency costs.…”
Section: Mediating Effect Of Randd Investmentmentioning
confidence: 86%
“…Furthermore, this study focuses on management decisions to disclose future-oriented information in the annual reports. Examining other managerial decisions such as the Research and Development (R&D) spending (Hassanein et al, 2021a(Hassanein et al, , 2022 and other channels of disseminating information such as social media disclosure (Hassanein et al, 2021b) provide avenues for future research. Furthermore, investigating whether futureoriented disclosure in the annual report leads to an information overloading issue (e.g.…”
Section: Futureoriented Disclosure In Kuwaitmentioning
confidence: 99%